Hyperhidrosis – pathogenesis and treatment methods - Sazanów-Lubelski, Jakub; Bergler-Czop, Beata Sylwia; Barasińska, Paulina; Noga, Natalia (Dermatology Review/Przegląd Dermatologiczny, 2018)
Hyperhidrosis is a condition characterized by excessive sweating which may have a primary or secondary cause. The diagnosis is facilitated by the guidelines of the Canadian Hyperhidrosis Advisory Committee. Prior to initiating treatment, the severity of the condition is determined based on the Hyperhidrosis Disease Severity Scale or objective examinations (Minor test or gravimetric method). The therapeutic options depend on the type of hyperhidrosis and are divided into topical, systemic and procedural modalities. The first-line drugs are topical preparations including aluminium salts, glycopyrrolate 2% and tannic acid solutions. Systemic therapies are based primarily on anti-cholinergic and β-adrenolytic drugs. Procedural therapies include botulinum toxin treatment, iontophoresis, laser therapy as well as techniques based on microwaves and ultrasounds. If these modalities fail, the remaining option is surgery, including sympathectomy or surgical removal of sweat glands.